Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3168/jds.2018-16129
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Chia seed extract enhances physiochemical and antioxidant properties of yogurt

Abstract: Yogurt is a healthy dairy food fermented by lactic acid bacteria (LAB). Because consumers demand healthier and more nutritious yogurt, numerous substances have been used to supplement yogurt. Chia seed has been reported to contain abundant phenolic compounds, dietary fiber, and n-3 fatty acids and therefore is a potential functional food additive. The aim of this study was to investigate the influence of chia seed extracts on the physicochemical and bioactive properties of set-type yogurt. Yogurt was fortified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 42 publications
(42 reference statements)
5
35
0
2
Order By: Relevance
“…Similarly, Liu (2018) observed that when Fuzhuan brick tea leaves were added to yogurts (1-3 g/100 mL), FCRC ranged from 15 to 65 mg/100 mL, and antioxidant activity as measured by the ABTS assay ranged from 20 to 85% radical inhibition. Gaglio et al (2019) added saffron (5 g/40 kg of yogurt) and found a mean FCRC of 18.5 mg of GAE/100 g and FRAP of 40.3 mmol of TE/100 g. Kwon et al (2019) used a chia extract obtained with ethanol or water to prepare yogurts and observed dose-dependent total phenolic content and antioxidant activity as measured by the DPPH and ABTS assays when extracts were added at 0.05 to 0.10 g/100 g. These results emphasize the remarks made by Granato et al (2018) that dairy foods should be the target of research regarding the addition of natural bioactive-rich extracts, aimed at decreasing the use of synthetic compounds.…”
Section: Characterization Of Yogurts With Lcementioning
confidence: 99%
“…Similarly, Liu (2018) observed that when Fuzhuan brick tea leaves were added to yogurts (1-3 g/100 mL), FCRC ranged from 15 to 65 mg/100 mL, and antioxidant activity as measured by the ABTS assay ranged from 20 to 85% radical inhibition. Gaglio et al (2019) added saffron (5 g/40 kg of yogurt) and found a mean FCRC of 18.5 mg of GAE/100 g and FRAP of 40.3 mmol of TE/100 g. Kwon et al (2019) used a chia extract obtained with ethanol or water to prepare yogurts and observed dose-dependent total phenolic content and antioxidant activity as measured by the DPPH and ABTS assays when extracts were added at 0.05 to 0.10 g/100 g. These results emphasize the remarks made by Granato et al (2018) that dairy foods should be the target of research regarding the addition of natural bioactive-rich extracts, aimed at decreasing the use of synthetic compounds.…”
Section: Characterization Of Yogurts With Lcementioning
confidence: 99%
“…The color quality of the yogurt samples was quantified by the three parameters including L * (lightness), a * (red‐green), and b * (yellow‐blue) by using a colorimeter (CHROMA METER CR‐400, Japan) (Kwon et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…This result is supported by the findings of Pop, Vlaic [34] who determined that the addition of 1.4% chia seed to yoghurt increased the number of lactic acid bacteria in comparison with the control sample. Besides, Kwon, Bae [35] reported that the addition of 0.1% chia seed water extract and chia seed ethanol extract into yoghurts significantly increased the number of lactic acid bacteria. Compared to the initial day, a statistical increase in titratable acidity values of CMY3 and GGY2 was observed at the end of the storage period (p<0.05).…”
Section: Evaluation Of Physicochemical Characteristics Of Yoghurt Sammentioning
confidence: 99%
“…In this regard, their findings coincided with our results about the behaviors of CSM and guar gum for yoghurt syneresis. Moreover, Kwon, Bae [35] revealed that 0.1% chia seed aqueous extract and ethanol extract improved water holding capacity in yoghurts due to the high reactivity of the polyphenols they contain, such as chlorogenic and caffeic acid. Overall however, the samples containing 2% CSM had remarkably lower syneresis in comparison to all other treatments (i.e.…”
Section: Syneresismentioning
confidence: 99%